2015
DOI: 10.5830/cvja-2015-031
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of symptomatic infantile heart disease at Louga Regional Hospital, Senegal

Abstract: ResuméLa prise en charge des cardiopathies infantiles congénitales ou acquises dans les pays d’Afrique au sud du Sahara posent encore d’énormes difficultés de diagnostic et d’accès au traitement notamment chirurgical. Les objectifs de ce travail rétrospectif étaient de déterminer la prévalence des cardiopathies observées en milieu pédiatrique au Centre Hospitalier Régional (CHR) de Louga, de décrire les différents types observés et de rapporter leur évolution à court terme.Durant la période d’étude, 1 Juillet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 3 publications
3
18
0
Order By: Relevance
“…The study reports an overall prevalence of 4.6‰. This rate is in the range of 4.3‰ and 14‰ reported in the literature in sub-Saharan Africa [4] [6] [8] [9]. When considering the types of heart disease, the study reveals a prevalence of congenital heart disease (CHD) and acquired (AHD) respectively 2.3‰ and 1‰.…”
Section: Epidemiologicallymentioning
confidence: 72%
See 4 more Smart Citations
“…The study reports an overall prevalence of 4.6‰. This rate is in the range of 4.3‰ and 14‰ reported in the literature in sub-Saharan Africa [4] [6] [8] [9]. When considering the types of heart disease, the study reveals a prevalence of congenital heart disease (CHD) and acquired (AHD) respectively 2.3‰ and 1‰.…”
Section: Epidemiologicallymentioning
confidence: 72%
“…Ngouala et al [4] reported comparable rates in 2015, 3% for congenital heart disease (CHD) and 1.3% for acquired heart disease (AHD). In 2006, Noa et al [10] in Cameroon also reported a prevalence of congenital heart disease (CHD) and acquired (AHD) comparable respectively of 2.78‰ and 2.36‰.…”
Section: Epidemiologicallymentioning
confidence: 99%
See 3 more Smart Citations